Islamic Social Capital in Cooperative-Based Community Empowerment (Case Study of Makmur Mandiri Cooperative, Padangsidimpuan City) - Anggi Rizkina Sari Siregar; Marliyah Marliyah; Juliana Nasution (Indonesian Journal of Islamic Economics and Finance, 2026)
Cooperative-based community empowerment depends not only on financial capital but also on the quality of social relations embedded in institutional practices. This study examines the role of Islamic Social Capital in community empowerment at the Makmur Mandiri Savings and Loan Cooperative, Padangsidimpuan City. Using a qualitative case study approach, data were collected through interviews, observation, and documentation. Findings reveal that the cooperative has operated stably and delivered tangible economic benefits through flexible capital access. Three core Islamic values underpin its social fabric: amanah (trustworthiness), reflected in transparent and accountable management; ukhuwah (brotherhood), expressed through sustained social bonds between managers and members; and ta‘awun (mutual assistance), manifested in economic and social support during hardship. Theoretically, this study extends Islamic Social Capital theory by demonstrating its operational mechanisms within a cooperative institution. Practically, it provides a replicable model for embedding Islamic values into cooperative governance to enhance sustainable member empowerment. These findings contribute to the limited literature on Islamic social capital in savings and loan cooperatives, particularly in the local context of North Sumatra.